2006
DOI: 10.1677/erc.1.00931
|View full text |Cite
|
Sign up to set email alerts
|

Sex-steroid regulation of vascular endothelial growth factor in breast cancer

Abstract: Angiogenesis is a key event, which occurs in both normal and pathological expansion of tissues and provides the nourishment necessary for growth. The role of angiogenic growth factors in breast pathology is rapidly gaining recognition since scientists and clinicians realized that these factors could function as molecular targets event 550 209822 for controlling tumor expansion. Vascular endothelial growth factor (VEGF) is a key regulator of angiogenesis. Although significant advances have been made in understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 183 publications
6
46
1
1
Order By: Relevance
“…This supports the hypothesis that progestins may promote the proliferation of latent breast tumor cells, which may contribute to the increased breast cancer risk associated with progestincontaining HRT [10,11,21,41]. Apigenin blocked MPAinduced proliferation, reducing levels of tumor cell proliferation to those observed in controls.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This supports the hypothesis that progestins may promote the proliferation of latent breast tumor cells, which may contribute to the increased breast cancer risk associated with progestincontaining HRT [10,11,21,41]. Apigenin blocked MPAinduced proliferation, reducing levels of tumor cell proliferation to those observed in controls.…”
Section: Discussionsupporting
confidence: 83%
“…As a result, the use of combination HRT has become controversial and recent epidemiological studies link the decline in HRT to reduced incidence of ductal carcinoma in situ, particularly hormone-receptor-positive invasive breast cancer [7][8][9][10]. Due to the rapid onset of tumor growth in postmenopausal women undergoing combination HRT, we and others have suggested that the progestin component promotes the progression of latent tumor cells or stimulates proliferation of cancer stem cells [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…VEGF is also known to augment capillary permeability (33). Although there have been several reports concerning estrogen regulation of VEGF in breast cancer, the findings are still controversial and the underlying mechanism remains unclear (35). In this study, western blotting analysis of biopsies from the hormone receptor-positive luminal-like tumors harvested 3 and 10 days after estradiol withdrawal showed more phosphorylation of VEGFR2 compared to controls.…”
Section: Discussionmentioning
confidence: 55%